Pengaruh Kepemimpinan Transformasional dan Kompensasi terhadap Produktivitas Pegawai Dinas Pertanahan Kutai Timur - Mursalim; Eko Nursalim; Zanuar Anwari (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
This research aims to determine the extent of the influence of transformational leadership and work compensation on employee productivity at the Land Office of East Kutai Regency. This type of research is classified as field research using a quantitative approach. This research uses complementary data collection techniques, namely the questionnaire technique to obtain research data through scoring from respondents, then the observation technique to directly observe activities taking place at the East Kutai Land Office, and finally the documentation technique to obtain additional supporting data needed in this research. The population in this study consists of 47 respondents, who are all employees of the East Kutai Land Office. Next, to analyze the data, the researcher used the multiple linear regression formula. The results of this study indicate that the transformational leadership variable has a positive but not significant effect on work productivity at the Kutai Timur Land Office by 15.1%. Furthermore, the work compensation variable has a positive and significant effect on employee work productivity at the East Kutai Land Office by 61%. Then, together, the transformational leadership variable and work compensation have a positive and significant impact on employee productivity at the East Kutai Land Office by 76.1%, while the remaining 23.9% is influenced by other variables not examined in this study.